From Corona Virus to Heartache: Investigating Acute Pericarditis after Covid-19 - Asmara, A Danang; Ramdani, Dadan; Setiawan, Deris Riandi; Priambodo, Ayu Prawesti; Mirwanti, Ristina (Indonesian Journal of Global Health Research, 2024)
Cardiovascular disorders have been associated with coronavirus disease 2019 (COVID-19). One of the emerging complications is acute pericarditis, characterized by inflammation of the pericardium. Pericarditis is a complication that arises after COVID-19 infection because the virus can cause widespread inflammation, including in the pericardium, the outer layer of the heart. Risk factors that may exacerbate pericarditis in COVID-19 patients include the severity of COVID-19 disease, an immunocompromised state, or an excessive immune system response to infection. The aim of the study is to describe a case of acute pericarditis that occurred after Severe Acute Respiratory Syndrom - Coronavirus 2 (SARS-CoV-2) infection. This study used a case study design. This study was conducted on one of the patients who experienced pericarditis after Covid-19. Researchers conducted nursing assessments and analyzed nursing data. Data analysis was carried out descriptively to describe the results of nursing assessment. A few days after experiencing SARS-CoV-2 pneumonia, 51-year-old Mr. S. developed chest pain that became more painful during exertion, and received a diagnosis of acute pericarditis. As a result, medical treatment was escalated with clinical improvement continuing to improve. Electrocardiography showed elevation in ST segment and depression in PR interval. Echocardiography showed grade I diastolic phase disruption. Acute pericarditis is a rare complication following viral infection. This report shows the assessment and management of acute pericarditis so as to prevent complications that can occur.